Immunological and Hematological Response to Local Transplantation of Stem Cells in Injured Radial Nerve of Dogs - Essa, Haidar H.; Jasim, Huda S.; Kadhim, Hameed A. (The Iraqi Journal of Veterinary Medicine, 2020)
The current study was carried out to investigate the immunological and hematological changes due to local transplantation of human umbilical cord-mesenchymal-stem cells (HUC-MSCs) and scaffold-stem cells (SSCs) into the injured radial nerve. Therefore, three equal groups of dogs were subjected to this study; experimental (EG), positive control (PCG) and negative control (NCG). At 1st week, dogs of EG were showed an obvious mobility dysfunction. At 2nd and 4th weeks, there were apparent improvements reported on general and physical activities as well as functional ability of forelimb with the presence of slight lameness that was cured completely at 5th week. Regarding to immunobiomarkers, insignificant differences were showed at 1st week. However, significantly increase in IgG and TNF-α, and decrease in IL-10 was reported at 2nd, 4th, and 6th weeks. Regarding to hematologic parameters, significantly increases were recorded in total WBCs from 2nd week onwards, lymphocytes and neutrophils at 2nd week, monocytes at the 2nd and 4th weeks, and total RBCs at the 8th and 16th weeks. Significant differences were not reported in values of PCV and Hb throughout this study. In conclusion, HUC-MSCs and SSCs confirmed high activities in supporting of immunological and hematological responses, and in restoration of nerve function